Southern Capitalism : The Political Economy of North Carolina, 1880-1980 - Wood, Phillip J., 1951- (Book collections on Project MUSE., 1986)
Southern Capitalism challenges prevailing views of Southern development by arguing that the persisting peculiarities of the Southern economy-such as low wages and high poverty rates-have not resulted from barriers to capitalist development, nor from the lingering influence of planter values. Wood argues that these peculiarities can instead be best understood as the consequence of a strategy of capitalist development, based on the creation and preservation of social conditions and relations conducive to the above-average exploitation of labor by capital. focusing on the evolving r.